The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/agronomy10040553
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Mowers Working in Narrow Spaces: A Possible Future Application in Agriculture?

Abstract: Autonomous mowers are becoming increasingly common in public and private greenspaces. Autonomous mowers can provide several advantages since these machines help to save time and energy and prevent operators from possible injuries. Current autonomous mowers operate by following random trajectories within areas defined by a shallow-buried boundary wire that has the purpose to generate an electro-magnetic field. Once the electro-magnetic field is perceived by the autonomous mower, the machine will stop and change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
(21 reference statements)
2
19
0
Order By: Relevance
“…The random operating pattern of the autonomous mower turned into frequent overlapping, leading to an overall higher working time to mow a given area compared to a systematic operating pattern. The autonomous mowers' efficiency was close to 37% for a surface with no obstacles [34], while in an area with many obstacles, such as the vineyard, the working efficiency of the machine results were even lower [25]. Despite a higher working time, during both years, the primary energy consumption of the innovative management system was lower compared to the primary energy consumption of the conventional management system.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The random operating pattern of the autonomous mower turned into frequent overlapping, leading to an overall higher working time to mow a given area compared to a systematic operating pattern. The autonomous mowers' efficiency was close to 37% for a surface with no obstacles [34], while in an area with many obstacles, such as the vineyard, the working efficiency of the machine results were even lower [25]. Despite a higher working time, during both years, the primary energy consumption of the innovative management system was lower compared to the primary energy consumption of the conventional management system.…”
Section: Resultsmentioning
confidence: 89%
“…Autonomous mowers are battery-powered machines designed to autonomously perform lawn mowing that offer high energy efficiency [20], with no local pollution from exhaust gasses and noise emissions, preventing operators from coming into contact with allergens [21,22]. Although not yet designed for agriculture purposes, autonomous mowers may improve vineyard floor management sustainability as a consequence of their reduced ground pressure [23], their high frequency of cut [24] and their ability to move between vine plants [25]. Continuous mowing has the potential to prevent weeds from excessive vertical development [26] and to encourage bermudagrass lateral growth [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The custom-built software calculates the area mowed by the autonomous mower over a given period of time, based on the distance traveled and the cutting width. The mowed area data were recorded every 15 min and are reported as a percentage of the total area [37].…”
Section: Assessmentmentioning
confidence: 99%
“…In this trial, significant reductions of power consumption and CO 2 emissions were observed compared to the ordinary technique. Despite designed for lawns mowing, autonomous mowers have shown promising results for agricultural purposes [28,37] due to their reduced size and high frequency of cut [38]. This last characteristic has the potential to exert a continuous mechanical control of both CC and weeds, preventing them from reaching an undesirable vertical growth [38].…”
Section: Introductionmentioning
confidence: 99%